2007
DOI: 10.2165/00044011-200727100-00007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Glucose Levels after??Initiation of Methylphenidate in??a??Patient Status Post-Cerebellar Tumour Resection

Abstract: Pharmacological intervention with methylphenidate to address the neurobehavioural deficits associated with various neurological disorders has increased during the past decade. One potential effect of methylphenidate use is its possible influence on serum glucose. This case report illustrates a significant post-intervention decrease in blood glucose levels subsequent to initiation of methylphenidate to address neurocognitive deficits, status post-acute cerebellar tumour resection, in a 38-year-old female with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Satterfield et al 12 found no association between prolonged administration (1–4 years) of methylphenidate to hyperactive boys regarding hematopoietic, endocrine (including glucose levels), hepatic, or cardiovascular functions analyzed in their study. However, Gontkovsky et al 13 reported a decrease of 26% in serum glucose values after methylphenidate initiation in a patient after a cerebellar tumor resection. Vitiello 14 did not find clinically significant changes in cardiovascular function in the majority of cases investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satterfield et al 12 found no association between prolonged administration (1–4 years) of methylphenidate to hyperactive boys regarding hematopoietic, endocrine (including glucose levels), hepatic, or cardiovascular functions analyzed in their study. However, Gontkovsky et al 13 reported a decrease of 26% in serum glucose values after methylphenidate initiation in a patient after a cerebellar tumor resection. Vitiello 14 did not find clinically significant changes in cardiovascular function in the majority of cases investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of lipid metabolism abnormalities is mainly genetic. The secondary causes of dyslipidemia are well‐known and include inappropriate lifestyle, liver disease, renal disease, and hypothyroidism 13 . The different drugs that are known to affect lipid metabolism include hormones (glucocorticoids, estrogens, and androgens), beta‐blockers, diuretics, and others 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature is lacking concerning the potential negative side effects and interactions of other medications prescribed for the management of psychiatric symptoms in children and adolescents, particularly the various psychostimulants utilised in the treatment of ADHD. Only one report in the literature deals with a potential negative interaction of methylphenidate with glipizide (Gontkovsky et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gontkovsky et al (14) reported a decrease o f 2 6 % i n s e r u m g l u c o s e v a l u e s a f t e r methylphenidate initiation in a patient post-cerebellar tumour resection. Being a neurostimulant, the possible linkage of methylphenidate to the cardiovascular system was investigated.…”
Section: Methylphenidate's Toxicitymentioning
confidence: 99%